GCT-48. OUTCOME OF CNS MALIGNANT NON-GERMINOMATOUS GERM CELL TUMORS (GCT) WITH AFP > 1000 ng/ml AT DIAGNOSIS TREATED ACCORDING TO SIOP CNS GCT 96. (4th December 2020) - Calaminus, Gabriele; Frappaz, Didier; Kortmann, Rolf-Dieter; Ajithkumar, Thankamma; Pietsch, Torsten; Vasiljevic, Alexandre; Ricardi, Umberto; Faure-Conter, Cecile; Timmermann, Beate; Alapetite, Claire; Murray, Matthew J; Garre, Maria Luisa; et al.
Abstract: Analysis of CNS MMGCT with AFP >1000 ng/ml (serum and/or CSF) at diagnosis, treated on trial in SIOP-CNS-GCT-96, revealed an inferior prognosis (32% 5-year progression-free survival) compared with AFP <1000 ng/ml (76%). As this patient group is small, to evaluate a bigger cohort, we revisited all patients treated according to SIOP-CNS-GCT-96, who were registered in the database until July 2015. Between October 1996 and July 2015, 373 patients with CNS MMGCT were registered. 48 patients (13%) presented with an AFP >1000 ng/ml at diagnosis. 41 patients were evaluable with a median observation time of 2.4 years; 6/41 received chemotherapy alone. Primary site, histological components (if available), metastatic status and outcome were evaluated. Primary site was pineal in 29/41, suprasellar in 6/41, bifocal 1/41 and other in 5/41 patients. 10/41 patients were metastatic at diagnosis. Four to five courses of standard PEI and radiotherapy (RT) or 2 standard and two intensified PEI (as for SIOP CNS GCT II) were administered in 32 patients. Two received less then 4x PEI and RT, 6 patients <6 years were treated with PEI (either standard or intensified) alone. 16/34 patients with PEI and RT are alive in CR; 2/6 patients without RT survived. Overall, 18/40 (45%) survived. 10–15% of CNS MGGCT are high-risk patients by diagnostic AFP, with the pineal as the main tumour site. Outcome of <50% survival is unsatisfactory. Further research, international cooperation and common data analysis is needed to identify additional risk factors and develop alternative treatment strategies.